Penggunaan Aplikasi Quizizz Dalam Evaluasi Pembelajaran Sejarah Kelas X IPA 2 SMA Negeri 9 Pontianak - Ellisya Sejarah; Andang Firmansyah; Haris Firmansyah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the use of the Quizizz application by teachers in evaluating history learning, starting from the design of the evaluation form, implementation and constraints using the Quizizz application for class X IPA 2 SMA Negeri 9 Pontianak. This study uses a descriptive qualitative research method. The data sources for this research were a history teacher and six students in class X IPA 2. The research location was at SMA Negeri 9 Pontianak, Jl. Tanjung Raya II, Komp. Integrated School, Kec. East Pontianak, Pontianak City. Data collection techniques used are observation, interviews and documentation. Data collection tools are observation sheets, interview guides, and documentation. Data analysis techniques researchers use data reduction, data presentation and drawing conclusions. To test the validity of the data researchers used triangulation. From the results of data analysis, researchers know that: (1) The teacher prepares a design for learning evaluation forms, introduces and guides how to use the Quizizz application. (2) Implementation of the use of the Quizizz application in evaluating history learning. (3) The use of the Quizizz application plays a major role in measuring students' abilities as well as providing feedback between teachers and students on the learning process.